Circular RNAs as potential biomarkers and therapeutics for cardiovascular disease - Wang,Weitie; Wang,Yong; Piao,Hulin; Li,Bo; Huang,Maoxun; Zhu,Zhicheng; Li,Dan; Wang,Tiance; Xu,Rihao; Liu,Kexiang (PeerJ, 2019)
Circular RNAs (circRNAs) are genetic regulators that were earlier considered as “junk”. In contrast to linear RNAs, they have covalently linked ends with no polyadenylated tails. CircRNAs can act as RNA-binding proteins, sequestering agents, transcriptional regulators, as well as microRNA sponges. In addition, it is reported that some selected circRNAs are transformed into functional proteins. These RNA molecules always circularize through covalent bonds, and their presence has been demonstrated across species. They are usually abundant and stable as well as evolutionarily conserved in tissues (liver, lung, stomach), saliva, exosomes, and blood. Therefore, they have been proposed as the “next big thing” in molecular biomarkers for several diseases, particularly in cancer. Recently, circRNAs have been investigated in cardiovascular diseases (CVD) and reported to play important roles in heart failure, coronary artery disease, and myocardial infarction. Here, we review the recent literature and discuss the impact and the diagnostic and prognostic values of circRNAs in CVD.
Keywords: Circular RNAs; Biomarkers; Cardiovascular disease